THE PATH OF THE MONTENEGRIN NATION FROM POLITICAL TO ETHNIC NATION - Todorovic, Vladica S. (Politeia, 2024)
In the article we discuss the process of formation of the Montenegrin nation. Our aim is to prove that the key moment, which will decisively influence the subsequent formation of the Montenegrin ethnic nation, is the recognition of the state of Montenegro at the Berlin Congress in 1878. The act marks the formation of Montenegrin political nation, the nation with its own state. Hence, we have come to a conclusion that the formation of Montenegrin political nation had a decisive influence on the future formation of Montenegrin ethnic nation and the attempts to characterise the Montenegrin ethnic nation with elements that make up a nation. The Montenegrins who express their allegiance to the Montenegrin ethnic nation also cherish the state of Montenegro. Nonetheless, the citizens of Montenegro who declare themselves as belonging to the Serbian ethnic nation also regard the state of Montenegro as sacred. Thus, they strongly defend their allegiance to the Montenegrin political nation but contrary to ethnic Montenegrins, they claim that Montenegro is a Serbian state. In that sense, the Serbs from Montenegro envision (possible) new unification with Serbia on a federal basis and not on a unitary basis. We have already witnessed that such a state, which existed from 1992 until 2006 under the name of the Federal Republic of Yugoslavia and, subsequently, Serbia and Montenegro, has no future. By not accepting (possible) unification on a unitary but on a federal basis, Serbs in Montenegro do not realize that due to such an attitude they are at risk of becoming members ofMontenegrin ethnic nation rather than pleading allegiance to the Montenegrin political nation.